TABLA DE DESARROLLO DEL ESTADO METAMÓRFICO EN Hyla labialis (2013)
The development of the metamorphic stage in Hyla labialis was studied at a temperature of 22•c with a constant frecuency of change ofthe medium every eight days. The larval (metamorphic) development comprised from the cul:rñl-> nation ofthe embrionic phase until the total reabsorption ofthe tail; the process is divided into twenty six stages, which are determined by morphological patterns, wich are proposed like a series ofreference comparative studies ofthe genus Hyla in Colombia. Even the larvae in the same stage of development vary in the absolute body dimensiorl:s. The relative quotiens of body dimensions are constant during most ofthe larval development and they are only altered from stage XXI when the anterior limb bud and thetail reabsorption begins.